Evaluation of Fly Ash Geopolymer on Asphalt Mixture Against Resilient Modulus Test - Sidek, Sharul; Bin Mohamad Taher, Mohammad Nasir (Recent Trends in Civil Engineering and Built Environment, 2021)
The continuous increase of traffic volume and traffic load in this modern era contributes to the asphalt pavement defect. High traffic volume and traffic load lead to the impact of the workability and quality properties of the asphalt pavement. As the traffic volume increases, the load on the pavement increases as well which causes pavement failure especially in the cracking and fatigue. This study aimed to investigate the stiffness of the asphalt pavement incorporating the fly ash geopolymer additives. The granite aggregate and bitumen grade 60/70 with the fly ash geopolymer at a concentration of 3%, 5%, 7%, 9%, and 11% of the total binder were used in this study to evaluate the Resilient modulus performance. The aggregate properties were determined using the flakiness index, elongation index, specific gravity, water absorption, and aggregate impact value respectively. The Resilient modulus test was performed using a Universal Testing Machine (UTM) at 25°C and 40°C test temperature following ASTM D4123-82 standard specifications. The study shows the resilient modulus of FAG modified samples was enhance approximately 30% compared to the controlled sample. Overall, it indicates the additions of FAG additives improve the stiffness of the asphalt mixture and increase the asphalt pavement endurance.